Efficacy of Written Corrective Feedback in the Short and Long Term - Samiei, Mitra; Tam, Shu Sim; Rouhi, Afsar (Journal of Modern Languages, 2017)
The purpose of this study was twofold: 1) to examine the general efficacy of different types of Written Corrective Feedback (WCF) on the errors of the target structure (past simple tense) in the short and long term and 2) to compare the possible difference in the effect that different WCF types might have on improving the target structure in the short and long term. One hundred and five EFL (English as Foreign Language) Iranian learners participated in this quasi-experimental study. They were divided into four experimental groups (20 in each) that received different WCF, that is, metalinguistic, direct, indirect, reformulation and a control group (n=25) that did not receive any feedback. The effects of the WCF types were measured using a Picture Description Test and an Error Correction Test as a pre-test, an immediate post-test, and a delayed post-test. It was found that all experimental groups performed better than the control group in the short term, but the metalinguistic and indirect WCF did not lose their effect in the long term. The findings from the delayed post-test confirmed the superiority of the metalinguistic and indirect WCF over the reformulation and direct WCF in the long term.